Juvenile criminal justice and its socio-educational purpose - Barletta Villarán, María Consuelo (2021)
The Criminal Code of Peru in Article 20.2 states that: "This exempt from criminal liability.'s Under 18" Differentiating than indicated in paragraph 1 which literally states is also exempt from liability: "The psychic anomaly that, severe disturbance of consciousness or suffer alterations in perception, which seriously affect your concept of reality does not possess the ability to understand the criminal nature of his act or to be determined by understanding", so we can say providing an interpretation scheme of the legislation in the light of existing principles of the Convention on the Rights of the Child (CRC) that the adolescent is exempt from criminal responsibility by the adult stage of development, growth and formation that governs his life.